Analysis of Oil Spill Distribution in Bintan Utara Waters Using Sentinel-1A Satellite Imagery - Akhmad Ferdinan Hairo; Mubarak Mubarak; Dessy Yoswaty; Bintal Amin; Ilham Ilahi (Jurnal Natur Indonesia, 2024)
Oil spills are a significant concern in the waters surrounding Bintan, Indonesia primarily due to tankers releasing ballast water before anchoring at the nearby port of Singapore, particularly during the north wind season. The region's high cloud cover presents challenges for detection efforts. However, the utilization of Sentinel-1 Satellite imagery offers a promising solution. This study aims to analyze the spatial distribution of oil spills in North Bintan waters using data collected from the Sentinel-1A satellite between December 2023 and January 2024. The study area includes Semelur Hamlet in Berakit Village, Bintan Regency. The analysis of data consists of oil spill detection and oil content. The results that the wind speed was measured within the range of 2 - 3.8 m/s, while the current speed fell within the range of 0.12 - 0.24 m/s. Additionally, the oil content was found to be less than 1 mg/l. The analysis conducted on the acquisition of December 6 - 24, 2023 revealed the presence of oil spills in four distinct areas. The spill areas were measured to be 1109 m2, 346 m2, 4258 m2, and 1491 m2, respectively. The windrose diagram reveals that the prevailing wind originates from the north northwest, accounting for 16% of the total wind occurrences. The average wind speed within this direction ranges from 3.6 - 5.7 m/s. Notably, the highest wind speed recorded exceeds 11.1 m/s and is observed to come from the north. The relationship between the process of image acquisition and the windrose diagram elucidates the impact of wind on the dynamics of oil spill movement.